Journal of Hospitality & Tourism Research. (Teller Road, Thousand Oaks, California : SAGE Publication, 2023)
u
u
u
u
u
u
u
u
u
u
u
u
b
u
Hospitality and Tourism Scholarship in Africa: A Literature-Based Agenda for Future Research -- Proposal for Employing User-Generated Content as a Data Source for Measuring Tourism Destination Image -- Let Photos Speak: The Effect of User-Generated Visual Content on Hotel Review Helpfulness -- Expatriate Adjustment and Engagement with Host Country Gastronomy: Investigating the Role of Identity Projects -- Influence of Tourism Seasonality and Financial Ratios on Hotels' Exit Risk -- An Analysis of the Impact of Short-Term Vacation Rentals on the Hotel Industry -- Editorial: 2021 ICHRIE Research Marathon -- Transformation of Consumer Expectations for Well-Being in Hospitality: A Systems Framework -- All That Glitters is Not Green: Impact of Biophilic Designs on Customer Experiential Values -- Be Adaptive to Stay: A Multidimensional Examination of Career Adaptability Among Hospitality Employees -- Disruptive Technologies and Innovation in Hospitality: A Computer-Assisted Qualitative Data Analysis Approach -- Destination Competitiveness and Human Development: The Compelling Critical Force of Human Agency -- The Intersection of Technology, Accessible Tourism and Tourists With Intellectual Disabilities: Proposing a Novel Conceptual Framework.
Includes bibliographical references.